STUDENTS’ READING ANXIETY TOWARDS THEIR READING COMPREHENSION PERFORMANCE IN LEARNING ENGLISH AS A FOREIGN LANGUAGE - Indrawati Indrawati (Scientia: Jurnal Hasil Penelitian, 2016)
The anxiety appeared during the process of reading foreign language texts is called as reading anxiety. However, most of the research focuses on the discussion of listening, speaking, and writing. Little attention has been paid to reading. Therefore, the present study attempts to fill the hidden empty space and explore the role of anxiety in foreign language reading. In this research the writer used the correlation statistical test to describe and measure the degree of relationship between two variables. So, in conducting this research, statistical number to correlate two variable of this research is needed, they are students’ reading anxiety and their reading comprehension. The main goal of the study is to find out whether or not there is a positive correlation between students’ reading anxiety and their reading comprehension of the third grade students of SMA Negeri 3 Pangkalpinang in the academic year 2016/2017.